Wajah Baru Pembelajaran Pendidikan Agama Islam Menggunakan Media Puzzle - Muhammad Fahmi; Ainul Halim; Abdul Mu'id (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2024)
This study is entitled "The New Face of Islamic Religious Education Learning Using Puzzle Media at SDN Windu Karangbinangun." This study aims to explore the use of puzzle media in Islamic Religious Education (PAI) learning and to determine students' responses to its use. We conducted the study at SDN Windu Karangbinangun, Karangbinangun District, Lamongan Regency. This study uses a qualitative descriptive approach, which collects data through observation, interviews, and documentation. The results of the study indicate that using puzzle media in PAI learning can increase students' learning motivation. This media allows students to learn in a beneficial way, as well as increase involvement and interaction in class. Students' responses to the use of puzzle media are very positive. They feel more motivated and interested in following PAI lessons. Puzzle media also helps them better understand the subject matter and improve their cognitive abilities. This study makes an important contribution to innovation in PAI learning methods by emphasizing the importance of using interactive and interesting media. We hope that educators and other researchers can use the results of this study as a reference to develop effective and enjoyable learning methods.